DNA sequence recognition in the minor groove by crosslinked polyamides: The effect of N-terminal head group and linker length on binding affinity and specificity - O'Hare, C. Caroline (The National Academy of Sciences, 2002)
Development of sequence-reading polyamides or “lexitropsins” with comparable DNA-binding affinities to cellular proteins raises the possibility of artificially regulated gene expression. Covalent linkage of polyamide ligands, with either a hairpin motif or crosslinking methylene bridge, has greatly improved binding affinity by ensuring their side-by-side register. Whereas hairpin polyamides have been investigated extensively, the optimized structure of crosslinked polyamides remains to be determined. This study examines a series of thiazole-imidazole-pyrrole (TIP) monomers and crosslinked dimers to evaluate the effects on selectivity and binding affinity of different N-terminal head groups attached to the leading thiazole ring and differing methylene linker lengths. Quantitative footprinting of a DNA sequence, containing potential match and mismatch sites for both maximum overlap and one-residue stagger binding modes, allowed measurement of binding constants at each putative site. Within an N-terminal amino TIP series, C7 and C8-linked compounds bound most strongly to these sites, whereas maximum binding affinity was observed for a C6 linker with a formyl head group. A C5 linker gave weak binding with either head group. A hydrogen or acetyl head group abrogated binding. Binding was confirmed by gel shift analyses. The highest specificity for the maximum overlap site over the one-residue stagger was observed with TIP-C7-amino. Selectivity of the leading thiazole was modulated by the head group, with N-terminal formyl TIP exhibiting up to 3-fold specificity for AGT over TGT, suggesting that N-formyl-thiazole may provide sequence discrimination of adenine over thymine. Moreover, the leading head group and methylene linker length significantly influences the binding characteristics of crosslinked polyamides.